Risk of hospitalization in a sample of COVID-19 patients with and without chronic obstructive pulmonary disease. (January 2023) - Myers, Laura C.; Murray, Richard; Donato, Bonnie; Liu, Vincent X.; Kipnis, Patricia; Shaikh, Asif; Franchino-Elder, Jessica
Abstract: Background and objective: Patients with chronic obstructive pulmonary disease (COPD) may have worse coronavirus disease-2019 (COVID-19)–related outcomes. We compared COVID-19 hospitalization risk in patients with and without COPD. Methods: This retrospective cohort study included patients ≥40 years, SARS-CoV-2 positive, and with Kaiser Permanente Northern California membership ≥1 year before COVID-19 diagnosis (electronic health records and claims data). COVID-19–related hospitalization risk was assessed by sequentially adjusted logistic regression models and stratified by disease severity. Secondary outcome was death/hospice referral after COVID-19. Results and discussion: Of 19, 558 COVID-19 patients, 697 (3.6%) had COPD. Compared with patients without COPD, COPD patients were older (median age: 69 vs 53 years); had higher Elixhauser Comorbidity Index (5 vs 0) and more median baseline outpatient (8 vs 4), emergency department (2 vs 1), and inpatient (2 vs 1) encounters. Unadjusted analyses showed increased odds of hospitalization with COPD (odds ratio [OR]: 3.93; 95% confidence interval [CI]: 3.40–4.60). After full risk adjustment, there were no differences in odds of hospitalization (OR: 1.14, 95% CI: 0.93–1.40) or death/hospice referral (OR: 0.96, 95% CI: 0.72–1.27) between patients with and without COPD. Primary/secondary outcomes did not differ by COPD severity, except for higher odds of hospitalization in COPD patients requiring supplemental oxygen versus those without COPD (OR: 1.84, 95% CI: 1.02–3.33). Conclusions: Except for hospitalization among patients using supplemental oxygen, no differences in odds of hospitalization or death/hospice referral were observed in the COVID-19 patient sample depending on whether they had COPD. Highlights: Whether patients with COPD have a higher risk of COVID-19–related hospitalization, mortality, and other adverse outcomes remains unclear. In this retrospective cohort study using electronic health records and claims data, odds of hospitalization or death/hospice referral did not differ in the sample of COVID-19 patients with and without COPD. COPD patients with prior supplemental oxygen use had greater odds of hospitalization but not death or hospice referral compared with patients without COPD.